A Study on Construction Waste Management of a Refurbishment Project in Kuala Lumpur - Y.Y, Lee; Mahmood, Noor Zalina (Malaysian Journal of Science, 2006)
Construction waste management is an important environmental issue. The huge volume and various compositions of construction waste have made its disposal a serious problem because it leads to environmental impacts such as landfill space and resource depletion. Greater concerns must be given to construction waste generation and management to reduce its burden to the environment. A refurbishment project site situated in Kuala Lumpur was selected for the study by regular site visits and initial environmental review (IER) was conducted to gather information on site activities and waste management practice. Environmental aspects and impacts caused by construction waste management were identified and their significance was assessed quantitatively and qualitatively. Four on-site sorting schemes were proposed and their practicality was discussed. The most significant environmental aspect was disposal of paper-based packaging waste followed by disposal of inert waste and plastic-based packaging waste, and recycling of steel containers off-site. The most preferred sorting scheme was to sort at specific work area for different types of work tasks. On-site sorting should be encouraged to facilitate construction waste reuse and recycling. Specific guidelines for construction waste management should be formulated and enforced to ensure sustainable construction.